Role of Cardiac Magnetic Resonance in Detecting Biventricular Apical Hypertrophic Cardiomyopathy - Nathan Zaher; Hammam Shereef; Rashid Al Hussain; John Dawdy; Diane Levine; M. Chadi Alraies (Case Reports in Cardiology)
Apical Hypertrophic Cardiomyopathy (ApHCM) is a rare variant of hypertrophic cardiomyopathy with a low prevalence in the general population. ApHCM with right ventricular involvement (BiApHCM) is largely unreported and may not be detected with conventional transthoracic echocardiogram (TTE) alone. Cardiac Magnetic Resonance (CMR) has been demonstrated to be a proficient imaging modality to diagnose BiApHCM. We present a case of BiApHCM that was diagnosed with TTE and further characterized by CMR. This imaging modality may be utilized more in the future to help diagnose and detect the prevalence of BiApHCM.